FRI0418 SECUKINUMAB PROVIDED SIMILAR EFFICACY IN MALES AND FEMALES WITH ACTIVE ANKYLOSING SPONDYLITIS OVER 52 WEEKS: POST HOC POOLED ANALYSIS OF THE MEASURE TRIALS. (June 2019) - Horst-Bruinsma, Irene van der; Richard, Corinne Miceli; Braun, Juergen; Bao, Weibin; Porter, Brian; Pournara, Effie
Abstract : Background: The burden of ankylosing spondylitis (AS) is reported to be higher in female patients (pts). In addition, females show less improvement in AS outcome measures as compared to males when treated with tumour necrosis factor (TNF) inhibitors. 1, 2 Currently, there are no data available on the efficacy of secukinumab (SEC) in males versus females. Objectives: To compare the efficacy of SEC in pts with active AS by gender (male vs female) from data pooled from four phase 3 studies (MEASURE 1-4). Methods: This post hoc analysis pooled data from the MEASURE 1-4 trials. Baseline (BL) demographics and disease characteristics were summarized across genders. Efficacy outcomes assessed at Week (Wk) 16 and 52 were ASAS20, ASAS40, ASDAS-ID, BASDAI, BASMI, BASFI, SF-36 PCS and FACIT-F. BL predictor analysis used multivariable logistic regression (binary variables) or generalized linear model (continuous variables) to assess the impact of gender as an independent variable on ASAS40, ASDAS-ID, and BASDAI at Wk 52, after adjusting for treatment group and other baseline factors in a pooled analysis across studies and treatment groups. Results: Overall, 647 males and 322 females who received SEC 300mg IV load (LD) (n=76), 150mg IV LD (n=199), 150mg s.c. LD (n=188), 150mg no LD (n=117), and placebo (n=389), respectively, were included in the analysis. At BL, significant differences in TNFi, HLA-B27, and smoking status were observed between genders. MASES scores were significantly higher in females; hs-CRP, BASMI-occiput to wall, and BASMI tragus to wall distance scores were significantly higher in males. Efficacy outcomes were generally similar in males and females (Figure 1 ). There was no significant impact of gender as an independent predictor of SEC efficacy at Wk 52 as measured by ASAS40 (Odds ratio [OR] 1.1; P=0.50), ASDAS-ID (OR 1.32; P=0.16) or change in BASDAI (treatment effect, -0.17; P=0.82). Conclusion: Similar efficacy outcomes were observed in male and female patients with active ankylosing spondylitis treated with secukinumab over 52 weeks. References: [1] Rusman Tet al, Int J Rheum Dis. 2018; 21: 836–42. [2] van der Horst-Bruinsma IEet al, Ann Rheum Dis. 2013;72:1221–4. Disclosure of Interests: Irene van der Horst-Bruinsma Grant/research support from: MSD, Pfizer, AbbVie, Consultant for: Abbvie, UCB, MSD, Novartis, Speakers bureau: BMS, AbbVie, Pfizer, MSD, Corinne Miceli Richard Grant/research support from: MSD, Pfizer, AbbVie, Biogen, UCB, Novartis, Consultant for: Abbvie, Novartis, BMS, Juergen Braun Shareholder of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Grant/research support from: Abbott, Bristol Myers Squibb, Celgene, Celltrion, Chugai, Johnson & Johnson, MSD, Novartis, Pfizer, Roche, UCB Pharma, Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Grant/research support from: Abbvie (Abbott), Amgen, Baxter, Biogen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Hexal, Janssen, Lilly, Medac, MSD (Schering-Plough), Mylan, Mundipharma, Novartis, Pfizer (Wyeth, Hospira), Roche, Sanofi-Aventis and UCB, Consultant for: Abbvie (Abbott), Amgen, Baxter, Biogen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Hexal, Janssen, Lilly, Medac, MSD (Schering-Plough), Mylan, Mundipharma, Novartis, Pfizer (Wyeth, Hospira), Roche, Sanofi-Aventis and UCB, Consultant for: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Consultant for: Abbott, Bristol Myers Squibb, Celgene, Celltrion, Chugai, Johnson & Johnson, MSD, Novartis, Pfizer, Roche, UCB Pharma, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Speakers bureau: Abbvie (Abbott), Amgen, Baxter, Biogen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Hexal, Janssen, Lilly, Medac, MSD (Schering-Plough), Mylan, Mundipharma, Novartis, Pfizer (Wyeth, Hospira), Roche, Sanofi-Aventis and UCB, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Weibin Bao Employee of: Novartis, Brian Porter Shareholder of: Novartis, Employee of: Novartis, Effie Pournara Shareholder of: Novartis, Employee of: Novartis